Legal Protection for Land Certificate Holders in the Complete Systematic Land Registration Program - Gaspersz, Frans Gerald Yacob; Berlianty, Teng; Uktolseja, Novyta (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Soil is not only a means of food production but also symbolizes social status. The Complete Systematic Land Registration Program (PTSL) is an effort to achieve legal certainty, although it still faces various obstacles such as lack of public awareness, land disputes, unclear village boundaries, and abuse of authority.Purposes of the Research: This research aims to study, analyze, and determine the legal certainty of complete systematic land registration (PTSL) as well as the legal strength of land rights certificates in the complete systematic land registration (PTSL) program.Methods of the Research: This research is a normative juridical research, using a descriptive analytical research type using primary, secondary and tertiary legal sources. The approach used is a statutory approach (Statute Approach), a conceptual approach (conceptual approach) and a case approach (Case Approach). The technique of collecting legal materials uses a literature study which is then analyzed qualitatively in order to answer the problems studied.Results Main Findings of the Research: The research results show that although the PTSL program aims to provide legal certainty for land rights holders, in reality, many certificate holders still face various obstacles such as administrative inefficiencies, unclear land boundaries, abuse of authority, and overlapping ownership claims, which result in a lack of assurance and legal protection for land certificate holders. The land rights certificates issued through this program, which are supposed to be strong legal protection instruments, often become sources of uncertainty and problems because they can be disputed by other parties claiming rights to the same land, thereby rendering the land certificates legally weak.